Students' Problem-Solving Skills in Polyhedral Geometry with GeoGebra Augmented Reality Support - Ruth Helen Simarmata; Muhammad Ali Buchari (Edumatika, 2026)
Background: Students often face difficulties in geometry learning, especially in topics that require students to interpret spatial objects and transform visual information into mathematical procedures including polyhedral geometry. Purpose: This study aims to analyze students’ mathematical problem-solving based on Polya’s framework in polyhedral geometry tasks within a GeoGebra Augmented Reality (AR)-supported. Method: This study used a mixed-method involving 30 eighth-grade students in Prabumulih. Data were collected through a mathematical problem-solving test, interviews, and classroom observation. Students’ responses were analyzed using a scoring rubric based on four stages of Polya’s problem solving: understanding the problem, devising a plan, carrying out the plan, and looking back. Findings: Most students fell into the medium problem-solving category (63.3%), with only 10% achieving the high category. While students performed best in understanding the problem, their primary difficulties lay in devising a plan and looking back. Implications: The integration of GeoGebra AR supports students in visualizing three-dimensional objects concretely. However, visual support alone is not sufficient to ensure complete problem-solving performance. Originality: The contribution of this study lies in a stage-by-stage diagnostic profile of students’ mathematical problem-solving in polyhedral geometry within a GeoGebra AR-supported learning environment.